Uveitis as a window to diagnosis of sarcoidosis – case report and review of the literature. Issue 4 (3rd July 2020) - Dhont, Sebastiaan; Leys, Mathias; De Sutter, Edward; Alaerts, Herwig; Van Moerkercke, Wouter
ABSTRACT: Sarcoidosis is a multisystem disease of unclear etiology with a variable clinical profile characterized by the presence of non-caseating granuloma in involved organs. The diagnosis is often challenging and based on clinical, radiological and anatomopathological data. Sarcoidosis can be benign and self-limiting, but some cases may follow a chronic, progressive course and result in severe morbidity. The disease has a predilection for the lungs and thoracic lymph nodes but can involve nearly any part of the body, possible more commonly in areas with contact to the external environment, such as the eyes and the skin. This paper is based on a case in which a recurrent uveitis led to the diagnosis of an underlying sarcoidosis.